New records of Elasmus (Hymenoptera, Eulophidae) species from Barrow Island, Western Australia - Gunawardene, Nihara; Taylor, Christopher (Pensoft, 2012)
Eleven species of Elasmus are recorded from Barrow Island in northern Western Australia, including nine not previously recorded for Western Australia. Elasmus curticornis sp. n.is described as new to science.